PENCEGAHAN VIRUS COVID-19 DI PUSKESMAS ANTANG KOTA MAKASSAR - A.Awaliya Anwar; Ebigael Ebigael; Patmi Patmi; Karmila Karmila (Lembaga Pengembangan Kinerja Dosen, 2021)
Corona virus is a virus that attacks the respiratory tract and causes high fever, cough, flu, shortness of breath and sore throat. The spread of this virus is so fast that it takes many lives in various countries. The spread of this virus is so fast that every day there are people who are exposed to or infected with this virus. So that an intensive understanding of the corona virus is needed so that counseling is carried out to provide education to them about preventing COVID-19 so that they can also know the impact of COVID-19. From the results of outreach activities to the community, it can be concluded that the community is able to carry out clean and healthy living behavior (PHBS) so that there is no transmission of disease and viruses.